Meaning and expression in Schopenhauer’s metaphysics of music - Barbosa, Ricardo (Sofia, 2026)
Schopenhauer conceived music as a genuinely metaphysical and cosmopolitan art, believing that in it the Will would gain a voice in a universal and immediately understandable language. His metaphysics of music is, however, as interesting as it is ambiguous. It is interesting because, among other aspects, it resists Hanslick’s criticism of the “aesthetics of feeling”, approaching his “formalism”. It is ambiguous because, on the one hand, while understanding music in relation to other arts, Schopenhauer tends to see it as a mimetic art, whose language is all the richer in meaning the more penetrating its reference to the most intimate aspects of things. On the other hand, while understanding music in and for itself, highlighting its autonomy and proximity to philosophy, Schopenhauer tends to see it as an epiphanic art, whose language is all the more expressive the more it allows us to hear the very dynamics of the Will. However, since Schopenhauer does not clearly distinguish between meaning and expression, the problem of musical semantics, which he thought he had solved, results in an insoluble aporia, before which metaphysics succumbs, without, however, dragging music itself down with it.
Keywords: Shopenhauer; metaphysics of music; musical aesthetics; expression and meaning